Comparative analysis of tobacco smoking intensity among young and middle-aged women of one administrative district of Tyumen in 1996-2016 - A. M. Akimov; A. A. Gakova; V. A. Kuznetsov (Кардиоваскулярная терапия и профилактика)
Aim. To study the changes of tobacco smoking intensity among young and middle-aged women of one administrative district of Tyumen in 1996-2016.Material and methods. Cross-sectional epidemiological studies were conducted on representative samples of women aged 25-64 years in 1996 and 2016. The category of smokers was ranked by age group and depending on the number of cigarettes smoked per day. The analysis included women of two categories — young age (25-44 years old) and middle age (45-64 years old). Women were considered high-intensity smokers if they smoked >10 cigarettes per day. According to this parameter, all smokers were divided into those with low and high smoking intensity.Results. According to the results, a negative 20-year dynamics was revealed — an increase in the tobacco smoking intensity in the population due to the category of young women. In young women over a 20-year period with a stable prevalence of tobacco smoking, a redistribution from low to high intensity of tobacco smoking was established — the prevalence of high-intensity smokers over low-intensity ones in 2016 with inverse proportions at the first screening. In middle-aged women, over a 20-year period, with a tendency towards an increase in tobacco smoking prevalence from the first to the second screening, the prevalence of low-intensity smokers over high-intensity smokers remains.Conclusion. Within the large-scale federal programs, it is necessary to direct efforts to reduce the intensity of tobacco smoking among women in middle-urbanized Siberian cities, focusing mainly on the category of young age.